Immobilization of U(VI) by stabilized iron sulfide nanoparticles: Water chemistry effects, mechanisms, and long-term stability - Duan, Jun; Ji, Haodong; Zhao, Xiao; Tian, Shuting; Xiaona Liu; Liu, Wen; Zhao, Dongye (Chemical Engineering Journal, 2020)
Carboxymethyl cellulose stabilized iron sulfide (CMC-FeS) nanoparticles have been shown promising for reductive immobilization of U(VI) in water and soil. This work aimed to fill some critical knowledge gaps on the effects of the stabilizer and water chemistry, reaction mechanisms, and long-term stability of stabilized uranium. The optimal CMC-to-FeS molar ratio was determined to be 0.0010. CMC-FeS performed effectively over pH 6.0–9.0, with the best removal being at pH 7.0 and 8.0. The retarded first-order model adequately interpreted the kinetic data, representing a mechanistically sounder model for heterogeneous reactants of decaying reactivity. The presence of Ca2+ (1 mM) or bicarbonate (1 mM) lowered the initial rate constant by a factor of 1.6 and 9.5, respectively, while 1 mM of Na+ showed negligible effect. Humic acid at 1.0 mg/L (as total organic carbon) doubled the removal rate, but inhibited the removal at elevated concentrations (≥5.0 mg/L). Fourier transform infrared spectroscopy, X-ray diffractometer, X-ray photoelectron spectroscopy, and extraction studies indicated that reductive conversion of UO22+ to UO2(s) was the primary reaction mechanism, accounting for  90% of U removal at pH 7.0. S2− and S22− were the primary electron sources, whereas sorbed and structural Fe(II) acted as supplementary electron donors. The immobilized U remained stable under anoxic conditions after 180 days of aging, while  26% immobilized U was remobilized when exposed to air for 180 days. The long-term stability is attributed to the protective reduction potential of CMC-FeS, the formation of uraninite and associated structural resistance to oxidation, and the high affinity of FeS oxidation products toward U(VI).
Keywords: Iron sulfide; Radionuclide; Reductive immobilization; Remobilization; Stabilized nanoparticle; Uranium removal